Biosynthesis of proresolving lipid mediators by vascular cells and tissues. Issue 8 (19th September 2017) - Chatterjee, Anuran; Komshian, Sevan; Sansbury, Brian E.; Wu, Bian; Mottola, Giorgio; Chen, Mian; Spite, Matthew; Conte, Michael S.
ABSTRACT: Recent evidence suggests that specialized proresolving lipid mediators (SPMs) generated from docosahexaenoic acid (DHA) can modulate the vascular injury response. However, cellular sources for these autacoids within the vessel wall remain unclear. Here, we investigated whether isolated vascular cells and tissues can produce SPMs and assessed expression and subcellular localization of the key SPM biosynthetic enzyme 5‐lipoxygenase (LOX) in vascular cells. Intact human arteries incubated with DHA ex vivo produced 17‐hydroxy DHA (17‐HDHA) and D‐series resolvins, as assessed by liquid chromatography‐tandem mass spectrometry. Addition of 17‐HDHA to human arteries similarly increased resolvin production. Primary cultures of human saphenous vein endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) converted 17‐HDHA to SPMs, including resolvin D1 (RvD1) and other D‐series resolvins and protectins. This was accompanied by a rapid translocation of 5‐LOX from nucleus to cytoplasm in both ECs and VSMCs, potentially facilitating SPM biosynthesis. Conditioned medium from cells exposed to 17‐HDHA inhibited monocyte adhesion to TNF‐α–stimulated EC monolayers. These downstream effects were partially reversed by antibodies against the RvD1 receptors ALX/FPR2 and GPR32. These results suggest that autocrine and/or paracrine signaling via locally generated SPMs in the vasculature may represent a novel homeostatic mechanism of relevance to vascular health and disease.—Chatterjee, A., Komshian, S., Sansbury, B. E., Wu, B., Mottola, G., Chen, M., Spite, M., Conte, M. S. Biosynthesis of proresolving lipid mediators by vascular cells and tissues. FASEB J . 31, 3393–3402 (2017). www.fasebj.org